2016
DOI: 10.14716/ijtech.v7i3.2844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plate Thickness and Casting Position on Skin Effect Formation in Thin Wall Ductile Iron Plate

Abstract: In producing Thin Wall Ductile Iron (TWDI) plate, special notice should be taken on the skin effect formation. Skin effect is a rim of flake interdendritic graphite formed in the surface. In a normal ductile iron casting, skin effect can be removed with machining process. Unfortunately this procedure cannot be applied in TWDI due to the thickness. This paper discusses the effect of casting design to the skin effect formation. Vertical casting design is used in this work. Variations are made in the thicknesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
2
0
6
Order By: Relevance
“…Aufderheiden [13] found that besides magnesium content, the type of sand also contributed to the formation of skin effect. Sulamet-Ariobimo [38] found that besides magnesium content, cooling rate also influences the formation of skin effect. [19] stated that skin effect tends to disturb the tensile properties.…”
Section: Skin Effectsmentioning
confidence: 99%
“…Aufderheiden [13] found that besides magnesium content, the type of sand also contributed to the formation of skin effect. Sulamet-Ariobimo [38] found that besides magnesium content, cooling rate also influences the formation of skin effect. [19] stated that skin effect tends to disturb the tensile properties.…”
Section: Skin Effectsmentioning
confidence: 99%
“…Aufderheiden [13] found that besides magnesium content, the type of sand also contributed to the formation of skin effect. Sulamet-Ariobimo [38] found that besides magnesium content, cooling rate also influences the formation of skin effect. Goodrich in Dix [19] stated that skin effect tends to disturb the tensile properties.…”
Section: Skin Effectsmentioning
confidence: 99%
“…Nama lapisan tersebut flake graphite rim anomaly [19] skin effect. Ketebalan lapisan maksimum yang pernah dicapai 20/0,2 mm [20]. Lapisan ini sangat mengganggu sifat tarik, menurunkan kekuatan & keuletan karena grafit serpih berperan sebagai konsentrasi tegangan & menjadi lokasi permulaan retak, lapisan kulit dihilangkan dengan proses permesinan.…”
unclassified
“…Kombinasi jenis inokulan dengan urutan inokulasi dipilih mendasarkan pada pengalaman pengecoran [16]. Meskipun pasir halus & cetakan dilapisi menyebabkan jarak lebih jauh logam cair, kekerasan & kekuatan sampel menurun [20] [26].…”
unclassified
See 1 more Smart Citation